Neuronal Nicotinic Acetylcholine Receptor Modulators from Cone Snails - Nikita Abraham; Richard J. Lewis (Marine Drugs, 2018)
Marine cone snails are a large family of gastropods that have evolved highly potent venoms for predation and defense. The cone snail venom has exceptional molecular diversity in neuropharmacologically active compounds, targeting a range of receptors, ion channels, and transporters. These conotoxins have helped to dissect the structure and function of many of these therapeutically significant targets in the central and peripheral nervous systems, as well as unravelling the complex cellular mechanisms modulated by these receptors and ion channels. This review provides an overview of α-conotoxins targeting neuronal nicotinic acetylcholine receptors. The structure and activity of both classical and non-classical α-conotoxins are discussed, along with their contributions towards understanding nicotinic acetylcholine receptor (nAChR) structure and function.